EFEKTIVITAS PEMBELAJARAN DARING DENGAN MEDIA CLASSROOM BAGI ANAK SD/MI - Akhmad Akhmad; Arisa Savinatun Najah; Taseman Taeman; Adheari Sya’ban Nugrohaji (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2022)
Nowadays, learning is increasing, especially literacy using the internet makes it a very important role to develop in our basic lives. Therefore, the education sector needs to utilize information technology in the learning process instansi education, various E-learning education platforms or online such as: edmodo, classroom, sway etc. But most learners use classrooms in addition to free classrooms are also easily accessible and efficient in internet access. Google Classroom is a apikasi that can be used for learning that is distributed by google. With its flexible and easy nature it is very beneficial for teachers and students to access it. The purpose of this scientific writing is to find out the effectiveness of classroom media when used in online learning. (Hapsari & Pamungkas, 2019), describing life at this time can not avoid in the development of technology in Indonesia is no longer as a password material anymore but has followed the main category of staples that terkhnologi must be dikuasi everyone, from the use of internet, multimedia and so forth. (Rochmah & Abdul Majid, 2018.